Protein synthesis inhibition by 8-oxo-12,13-epoxytrichothecenes - Ehrlich, Kenneth C.; Daigle, Kim W. (Biochimica et biophysica acta, 1987)
The Fusarium mycotoxin, 4-deoxynivalenol, is an abundant, natural contaminant of corn and wheat. 8-Oxo-12,13-epoxytrichothecenes related to 4-deoxynivalenol were synthesized; they either lacked the 7-hydroxyl but contained a hydroxyl at C-4 (7-deoxynivalenol) or lacked substituents at C-3 and C-7 (3,7-dideoxynivalenol). The ability of these synthetic analogs and their acetylated derivatives to inhibit protein synthesis by cultured mammalian cells was compared to that of 4-deoxynivalenol. Whereas the 50% inhibitory dose (ID50) for murine erythroleukemia cells was about 1 μg/ml for 4-deoxynivalenol and 3,7-dideoxynivalenol, all of the other analogs were at least 10-fold less potent. When tested at their ID50 dose, all of the 8-oxotrichothecenes, except 4-deoxynivalenol and 3,7-dideoxynivalenol, caused polysome ‘run-off’, indicating that, at this dose, they are inhibitors of polypeptide chain initiation. With 4-deoxynivalenol and 3,7-dideoxynivalenol, polysomes remained at control levels indicating that these toxins prevent polypeptide chain elongation. From these results and comparisons to previous studies of 8-oxo-12,13-epoxytrichothecenes (trichothecolone, trichothecin, nivalenol and fusarenone X), trichothecenes with substituents at both C-3 and C-4 predominantly inhibit polypeptide chain initiation, whereas those lacking one substituent at either site are inhibitors of chain elongation.